Optimization of Mobile Phase Modifiers for Fast LC-MS-Based Untargeted Metabolomics and Lipidomics - Cajka, Tomas; Hricko, Jiri; Rudl Kulhava, Lucie; Paucova, Michaela; Novakova, Michaela; Kuda, Ondrej (International journal of molecular sciences, 2023)
Liquid chromatography-mass spectrometry (LC-MS) is the method of choice for the untargeted profiling of biological samples. A multiplatform LC-MS-based approach is needed to screen polar metabolites and lipids comprehensively. Different mobile phase modifiers were tested to improve the electrospray ionization process during metabolomic and lipidomic profiling. For polar metabolites, hydrophilic interaction LC using a mobile phase with 10 mM ammonium formate/0.125% formic acid provided the best performance for amino acids, biogenic amines, sugars, nucleotides, acylcarnitines, and sugar phosphate, while reversed-phase LC (RPLC) with 0.1% formic acid outperformed for organic acids. For lipids, RPLC using a mobile phase with 10 mM ammonium formate or 10 mM ammonium formate with 0.1% formic acid permitted the high signal intensity of various lipid classes ionized in ESI(+) and robust retention times. For ESI(-), the mobile phase with 10 mM ammonium acetate with 0.1% acetic acid represented a reasonable compromise regarding the signal intensity of the detected lipids and the stability of retention times compared to 10 mM ammonium acetate alone or 0.02% acetic acid. Collectively, we show that untargeted methods should be evaluated not only on the total number of features but also based on common metabolites detected by a specific platform along with the long-term stability of retention times.
Keywords: LC-MS; modifiers; metabolomika; Metabolomics; optimization; mobile phase; lipidomics; Acetic Acid; kyselina octová; Lipidomics; Tandem Mass Spectrometry; chromatografie kapalinová; formiáty; metabolomics; additives; mass spectrometry; tandemová hmotnostní spektrometrie; Formates; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, Liquid; lipidomika; Spectrometry, Mass, Electrospray Ionization; liquid chromatography